1987
DOI: 10.1002/hlca.19870700414
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects on Reaction Rates. Part IX. Force‐Field Parameters for Bridgehead and Rigid Tertiary Carbenium Ions

Abstract: Molecular-mechanics calculations for strain of carbenium ions are tested using Bentley's unified reactivity scale for bridgehead solvolysis as reference. Excellent correlations are obtained for solvolytic bridgehead reactivity with the calculated steric-energy difference (?Est) between substrate (R--H or R--OH) and cation (R+). After adjustment of appropriate force-field parameters, the approach is successfully extended to the rigid, but planar cations derived from structures 15-20; however, the general set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The 7-methyl-7-norbornyl derivatives exhibited significant deviations from the strain-reactivity plot, the cation being apparently too strained [9]. More detailed inspection of the calculated structures revealed that the force-field calculations attributed an unrealistic bond angle of 110.7" to the cationic centre, while semi-empirical methods (MIND0/3) and ah initio calculations (STO-3G) resulted in bond angles of only 98" and 99.5", respectively [9] [lo]. This indicates, that the parametrization is not valid, when large deviations from the ideal bond angles are involved.…”
mentioning
confidence: 98%
“…The 7-methyl-7-norbornyl derivatives exhibited significant deviations from the strain-reactivity plot, the cation being apparently too strained [9]. More detailed inspection of the calculated structures revealed that the force-field calculations attributed an unrealistic bond angle of 110.7" to the cationic centre, while semi-empirical methods (MIND0/3) and ah initio calculations (STO-3G) resulted in bond angles of only 98" and 99.5", respectively [9] [lo]. This indicates, that the parametrization is not valid, when large deviations from the ideal bond angles are involved.…”
mentioning
confidence: 98%
“…In the case of 35 a correction of -6.93, based on comparison of calculations with 34 was used. The strain-reactivity correlations are of log kCalc = -AAE,t + B (3)(4)(5)(6) The quality of the fit is characterized by the correlation coefficient, r, and by the standard deviation of the experimental points from the regression line, c. The parameters for t h e correlations a r e summarized i n Table 11. The d a t a for t h e nonbridgehead compounds are shown in Figure I, where the MM2 results are indicated by crosses, and the BIGSTRN calculations by circles.…”
mentioning
confidence: 99%